The Political Socialization For Gay Young Adults (A Case Study On Legislative Election In Yogyakarta) - Wulan Widyasari, Wulan Widyasari; Susilastuti Dwi N, Susilastuti Dwi N (2015)
Political socialization, actually, is an investment of political values from one generation to the next generations. The purpose is to increase the political participation. Political socialization must take place continuously to all groups of societies. Lesbian Gay Bisexual Transgender (LGBT) group is a one of minority groups in our society, usually they are not accepted by the society, and they used to be forgotten in political socialization. However, in 2014 legislative election in Yogyakarta City of Indonesia, that elects Local Parliament (DPRD), House of Representatives (DPR) and Regional Councils (DPD) members; the LGBT people becomes a spotlight for the general election commissions (KPU) in Yogyakarta City. KPU has many methods to attract them in legislative election. One of their methods is doing political socialization. So, in this research we want to see how LGBT people think about the political socialization. The research method is focus group discussion to gay young adults as part of LGBT group. We pick those gay young adults as our informant because of their participation in general election and their knowledge about politics. Based on the research using descriptive analysis, it found that political socialization to LGBT group by KPU is not optimal; KPU cannot optimize the participation of LGBT group to become voter in legislative election. The reasons are: (1) LGBT group is unorganized group, because there is no data about them; (2) The socialization is not maximal because the political message is limited to call of their suffrage not to enlarge the political participation; (3) The candidates have no intention to create a program dedicated to the LGBT group. Based on the results, this political socialization method cannot be applied. The FGD results show that political socialization must start from political education to open the frame of view about LGBT group because their presence is needed for the sustainability of the nation.